A facile chemical method for the synthesis of 3C–SiC nanoflakes. Issue 26 (23rd February 2016) - Dragomir, Mirela; Valant, Matjaz; Fanetti, Mattia; Mozharivskyj, Yurij
Abstract : A facile chemical method for the synthesis of high specific surface area 3C–SiC nanoflakes in a NaCl powder template is presented. Abstract : A facile chemical method for the synthesis of 3C–SiC nanoflakes is presented. The process involves the pyrolysis of polycarbosilane (PCS) at 700 °C, in a NaCl powder template, followed by thermal treatment at 1200 °C. The salt is easily removed by washing with water. The morphology of the SiC particles is found to be dependent on the NaCl/PCS weight ratio and by carefully tuning this ratio, different SiC structures can be obtained. While at NaCl/PCS ratios < 40 : 1 micrometer-sized particles with a foamy like structure result, a NaCl/PCS ratio of 40 : 1 is crucial for the formation of 3C–SiC nanoflakes. These nanoflakes are less than 5 nanometers thick, have a high specific surface area of 169 m 2 g −1 and a high total pore volume of up to 0.75 cm 3 g −1 . This method could open a simple, versatile and robust way for the production of SiC nanostructures. Such a facile synthetic method could bring nanostructured SiC one step closer to the ultimate goal of practical applications.